URBAN HERITAGE CONSERVATION IN ACEH, INDONESIA: CONSERVINGPEUNAYONG FORTOURISM - Haryo Winarso (ASEAN Journal on Hospitality and Tourism, 2010)
It has been more than a half decade that the very destructive tsunami hit Banda Aceh, the capital city of Nanggroe Aceh Darussalam Province, located at the northern part of Sumatra Island. So far the urban planning and development in the city is focusing on reconstruction and rehabilitation, which can be absolutely understandable considering the devastating impact of tsunami at that time, however as the time passes by, a new intention has to be created to the conservation effort not only to uphold the value that Aceh once had, but also as an attraction to boost tourism.The paper argues that, despites some challenges in the interpretation and institution side, Puenayong would be the suitable place for conservation in Banda Aceh. Peunayong old shop-houses still retain the heritage architectural value. The long history of the area and the typical old Chinese architectural type of shop-houses make the area just the place for conservation. The regular maintenance by the owner such as painting, cleaning, and other efforts to protect old materials from decay have enabled this old shop-houses still stand at its architectural value today. As the economic value of the area is now increasing, reuse strategy could be used to maintain the character and the architectural value of the shop-houses and at the same time enhancing the environment quality of the site for tourist attraction.